Fluoroscopic-Assisted Olecranon Fracture Repair in Three Dogs - Stephen C. Jones; Daniel D. Lewis; Matthew D. Winter (Case Reports in Veterinary Medicine)
Olecranon fractures in dogs are often both comminuted and intra-articular. Anatomic reduction and stable internal fixation are thus paramount to achieving primary bone healing and mitigating the development of posttraumatic osteoarthritis. Intraoperative fluoroscopy can be useful to confirm accurate fracture reduction and facilitate precise implant placement, potentially reducing the surgical exposure required and additional trauma. Despite widespread use in human surgery, reports of fluoroscopic-assisted fracture repair in dogs are limited. Presented here are three dogs in which intraoperative fluoroscopy was used to facilitate accurate olecranon fracture reduction and implant positioning. The olecranon fractures appeared to heal by primary bone union, although the anconeal process failed to obtain osseous union in one dog. Despite the development of mild-to-moderate osteoarthritis in all three dogs, and the nonunion of the anconeal process in one dog, the clinical outcome was considered successful with all dogs subjectively free of lameness at long-term follow-up evaluation. Intraoperative fluoroscopy was found to be a useful modality during fracture reduction and implant placement in dogs with olecranon fractures.